Piston Engine Modelling for Hydrogen Fueled Composite Cycle Engines. Issue 1 (1st February 2022) - Nickl, M.; Winter, F.; Gümmer, V.
Abstract: In order to achieve aviation's ambitious emission reduction targets specified by ACARE [1] radical changes in propulsion system concepts will be necessary. To fulfill the goal of carbon dioxide emission neutrality in 2050 and beyond, plenty propulsion system concepts are currently under investigations, mainly focusing on batteries and hydrogen as energy source. Especially for long range aircraft applications, hydrogen might by favorable due to its outstanding specific gravimetric energy density. Therefore, the Composite Cycle Engine (CCE) concept should be evaluated for hydrogen combustion. In a first step, the applied time resolved 0D piston engine performance simulation model of the CCE is adapted for hydrogen combustion. For example, the heat transfer and combustion characteristics of kerosene and hydrogen combustion differ significantly and require specific modeling approaches. The current publication illustrates the piston engine performance simulation model and the modifications needed to account for hydrogen combustion. Furthermore, results of validation case calculations as well as initial sensitivity studies of the hydrogen fueled piston engines model are presented and discussed in the CCE context. For example, sizing effects and the influence of valve timing on piston engine performance will be evaluated.